Pengaruh Persepsi Tentang Koperasi Dan Pengetahuan Perkoperasian Terhadap Minat Mahasiswa Prodi Pendidikan Ekonomi Menjadi Anggota Kopma â€œAmanahâ€ - Nailariza Umami; Thesia Maradani (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2020)
Kopma Amana In this study using quantitative research, the population was 59 students. The sampling technique uses saturated sampling technique. Data collection techniques using a closed questionnaire method that has been tested with a validity test and reliability test. The data analysis technique used is multiple linear regression, t test F test. In this study the independent variables X1 (perception of cooperatives), X2 (Cooperative Knowledge) and for the dependent variable Y (Interest of students of economic education study programs become Kopma members). The results of this study indicate that partially Perception about cooperatives (X1) affects the interest of economic education study program students becoming members of Kopma (Y) with a tcount of 6.359 ttable 2.004 while Cooperative Knowledge (X2) influences the interests of economic education study program students becoming Kopma members ( Y) with a value of 2.033 t table 2.004. Simultaneously there is the Influence of Perception about cooperatives and Cooperative Knowledge on the interests of students of economic education study programs becoming Kopma members with a value of Fcount 32.403 Ftable 3.18. The correlation coefficient R of 0.745 and the determinant value in the Adjusted R Square column of 0.538 or 43.8% change in the variable Y is influenced by changes in variable X1 and variable X2. While the remaining 46.2% is influenced by other variables outside this study.